Difficult-to-Treat Resistance in Gram-negative Bacteremia at 173 US Hospitals: Retrospective Cohort Analysis of Prevalence, Predictors, and Outcome of Resistance to All First-line Agents. (23rd July 2018) - Kadri, Sameer S; Adjemian, Jennifer; Lai, Yi Ling; Spaulding, Alicen B; Ricotta, Emily; Prevots, D Rebecca; Palmore, Tara N; Rhee, Chanu; Klompas, Michael; Dekker, John P; Powers, John H; Suffredini, Anthony F; et al.
Abstract: Background: Resistance to all first-line antibiotics necessitates the use of less effective or more toxic "reserve" agents. Gram-negative bloodstream infections (GNBSIs) harboring such difficult-to-treat resistance (DTR) may have higher mortality than phenotypes that allow for ≥1 active first-line antibiotic. Methods: The Premier Database was analyzed for inpatients with select GNBSIs. DTR was defined as intermediate/resistant in vitro to all ß-lactam categories, including carbapenems and fluoroquinolones. Prevalence and aminoglycoside resistance of DTR episodes were compared with carbapenem-resistant, extended-spectrum cephalosporin-resistant, and fluoroquinolone-resistant episodes using CDC definitions. Predictors of DTR were identified. The adjusted relative risk (aRR) of mortality was examined for DTR, CDC-defined phenotypes susceptible to ≥1 first-line agent, and graded loss of active categories. Results: Between 2009–2013, 471 (1%) of 45011 GNBSI episodes at 92 (53.2%) of 173 hospitals exhibited DTR, ranging from 0.04% for Escherichia coli to 18.4% for Acinetobacter baumannii . Among patients with DTR, 79% received parenteral aminoglycosides, tigecycline, or colistin/polymyxin-B; resistance to all aminoglycosides occurred in 33%. Predictors of DTR included urban healthcare and higher baseline illness. Crude mortality for GNBSIs with DTR was 43%; aRR was higher for DTR than for carbapenem-resistant (1.2; 95% confidence interval, 1.0–1.4; P = .02), extended-spectrum cephalosporin-resistant (1.2; 1.1–1.4; P = .001), or fluoroquinolone-resistant (1.2; 1.0–1.4; P = .008) infections. The mortality aRR increased 20% per graded loss of active first-line categories, from 3–5 to 1–2 to 0. Conclusion: Nonsusceptibility to first-line antibiotics is associated with decreased survival in GNBSIs. DTR is a simple bedside prognostic measure of treatment-limiting coresistance. Abstract : Resistance to all first-line agents or difficult-to-treat resistance (DTR) was observed in 1% of gram-negative bacteremias. DTR was identified at half the hospitals; nearly 80% of patients with DTR received "reserve" agents. Mortality risk increased with decreasing active first-line categories.